Evaluasi Kesesuaian Lahan untuk Tanaman Jagung di Desa Saentis, Percut Sei Tuan - Elfayetti, Elfayetti; Herdi, Herdi (Universitas Negeri Medan, 2015)
This research aims to indentify the potency and suitability of land for cropping corn, and considering suitability of given input with limiting factors. The research have taken place since May to October 2006 in Saentis Village, District of Percut Sei Tuan. It focus on three types of land such as Alluvial, Regosol, and Organosol which are placed on 4 metres above sea level. By using method of des-criptive survey and sampling of the three land types, resulting that there is a tight significant relation between characteristic of land and production of corn. On the type of S3 m Alluvial with 33 of land index, including marginal suitable with middle level of limiting factors, at KTK, N total and P is available. Through giving urea and TSP, and adding organic materials, there was a shifting of class to S2 m which is marginal suitable with middle limiting. On the Regosol type of land, class of suitability of land categorized S3 m and 34 index of land, categorized marginal suitable with middle level of limiting factors, N total, and P is available. With adding anor-ganinc and organic materials, there was elevating one class to suitability level became S2 m (suitable). On type of Organosol, suitabi-lity of land categorized S2 and 74 of land index, categorized suitable with one limiting factor of availability of P, but if adding anor-ganic material added, suitability of land can be increase to one level become S1 (most suitable).